Special Features and Dynamics of the Mental States of Personality in Crisis Conditions - Uvarova, Svitlana (Psychological Prospects Journal, 2016)
The paper demonstrates the relevance of studying the specific features of traumatic experiences of personality who is in crisis conditions. The analysis of the substantial and dynamic aspects of the mental states caused by crisis events is carried out in the paper. The analysis of the topical areas of psychological science engaged into studying the influence of crisis situations on a person’s mental functioning is conducted. The paper defines psychological meaning of such concepts as stress, acute stress reaction, traumatic stress, post-traumatic stress disorder in the context of the process of emergence of the traumatic consequences of crisis events. The main approaches to specification of forms, levels and stages of stress experience are presented. The concept of such terms as “eustress” and “distress” is defined. The characteristic of the main situational reactions to a stressful event is presented. The analysis of the dynamics of the symptoms on set in the first days after the psycho-traumatic event is carried out and the stages of development of psychological experiences are described. The psychological aspect of traumatic stress is revealed and its main phases are considered. The main characteristics of trauma specifying the emergence of traumatic stress are explained. Special features of traumatic memories are defined (inconsistency, heterogeneity, a lack of significant fragments of the traumatic event, the brightness of images, and strong, exhausting emotions, physical feelings, etc.). Specific features of the developmentof post-traumatic stress disorder, as well as its specific symptoms, types and clinical course are examined. Keywords: crisis conditions, traumatic events, stress, acute stress reaction, traumatic stress, post-traumatic stress disorder.